Intelligent Revenue Operations Platform Using AI, NLP, and Machine Learning - Chejarla, Laxmi (International Journal of Computing and Engineering, 2025)
The intelligent revenue operations platform integrates artificial intelligence, natural language processing, and machine learning to transform fragmented business processes into cohesive, automated workflows. This platform addresses critical challenges in lead management, quote-to-cash processes, and compliance requirements by implementing autonomous company research, intelligent classification algorithms, and adaptive workflow automation. Upon identifying a new lead, the system performs comprehensive research across multiple sources, conducts sophisticated profile analysis, determines appropriate industry classifications, and evaluates transaction behaviors—all without manual intervention. The architecture extends through the entire revenue lifecycle, automating quoting, contract generation, order processing, and revenue recognition while maintaining regulatory compliance. Implementation experiences across SaaS and manufacturing industries demonstrate significant efficiency improvements, enhanced decision-making capabilities, and measurable financial benefits. The system's modular design and integration methodology enable adaptation to diverse organizational contexts while addressing data quality, system integration, and change management challenges